2018
DOI: 10.1029/2018jd028334
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Vertical Water Vapor Transport for TC Ingrid (2013)

Abstract: Vertical water vapor transport is examined for tropical cyclone (TC) Ingrid (2013), a Category 1 storm in the Gulf of Mexico that contained deep convection, including numerous overshooting tops. The study employs high-resolution numerical simulations using the Weather Research and Forecasting model with a smallest grid spacing of 1.33 km and a model top of 10 hPa (~31 km) that extends into the lower stratosphere. Area-averaged values of vertical motion, water vapor content, its temporal change, and vertical wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(45 citation statements)
references
References 114 publications
7
38
0
Order By: Relevance
“…This suggests that vertical flux (by itself) leads to increasing chemical concentrations. Current results for water vapor are consistent with prior TC studies that have found a positive net water vapor flux throughout the troposphere (e.g., Allison et al, ; Wang, ). However, to our knowledge, this is the first study to calculate CO and O 3 flux profiles for a TC.…”
Section: Model Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that vertical flux (by itself) leads to increasing chemical concentrations. Current results for water vapor are consistent with prior TC studies that have found a positive net water vapor flux throughout the troposphere (e.g., Allison et al, ; Wang, ). However, to our knowledge, this is the first study to calculate CO and O 3 flux profiles for a TC.…”
Section: Model Resultssupporting
confidence: 90%
“…Areas of the cells at tropopause altitude are all less than 0.4% of the total area of Mireille. Their heights above the tropopause range from 0.3 to 1.5 km (16.3 km to 17.5 km above sea level), consistent with previous studies (e.g., Allison et al, ; Pan et al, ; Tao & Jiang, ). However, they are slightly higher than those reported for Mireille by NE96 who found tops exceeding 15.5 km based on observed cloud top temperatures and vertical temperature profiles from the Japanese Geostationary Meteorological satellite.…”
Section: Model Resultssupporting
confidence: 90%
See 3 more Smart Citations